Comportamiento agronómico de ocho híbridos de sandía (citrullus lanatus schard.) en el campus de la ESPAM-MFL. 2011 - Cantos Loor, Javier Fernando (2012)
This research was carried out since September to December from 2011, at the ESPAM MFL campus, located at place El Limon, parroquia Calceta, province of Manabí, located geographically to 00o 49' 23'' of Southern Latitude and 80o 11' 01''of Length West and to 15 msnm's altitude; it had some objectives like, evaluate the performance of eight crossbreeds' agronomic characteristics of watermelon. We used a blocks totally at random design with five repetitions, the variables under consideration matched were number of fruits for plant, for plot of land and for hectare, weight, length and diameter of fruit, yield for plot of land and for hectare, thickness of the bark and degrees brix. In addition to the complementary variables; were days to the emergency, percentage of germination, days to flowering and days to the harvest, color of pulp and color of bark, downy mildew, white fly and virus diseases. The statistical results shauced the highest fruit for plants was the G-8330 crossbreed with 4.91 kg, while, American Sweet crossbreed showed 1.84 fruits for plant, the high average for plant of land with 30,61 kg and 14,577.14 kg/Ha, also, this crossbreed was very precocious to the harvest. That is a characteristic desirable to improve the crop production cast. This crossbreed got a profitability of 1817, 42 USD and 64, 32 % ofrate of marginal return.